Prevention of catheter-associated urinary tract infection in neurological post-operation patients: a best practice implementation project. (June 2019) - Liang, Ching-Chuan; Huang, Tzyy-Jen; Yang, Shu-Hua; Su, Jui Yuan; Mu, Pei-Fan; Curia, Marianne
ABSTRACT: Objective: The objective of this evidence based implementation project was to promote evidence based practice in the prevention of catheter-associated urinary tract infection (CAUTI) in the neurology and neurosurgery units of a Taipei hospital. Introduction: Catheter-associated urinary tract infection has been associated with increased morbidity, mortality, hospital costs and length of stay. Urinary drainage systems are often reservoirs of infection in patients, thus effective prevention of CAUTI requires an evidence-based approach. The CAUTI incidence in the neurosurgery units of the hospital was 1.86–2.69% urinary catheter days, which ranked as medium when compared to the entire hospital. Method: A clinical audit was undertaken using the Joanna Briggs Institute Practical Application of Clinical Evidence System tool, based on eight audit criteria that represented best practice recommendations for CAUTI. A baseline audit of the neurology and neurosurgery units was performed, followed by the implementation of multiple strategies throughout a 20-week period. A follow-up audit was undertaken after this to assess changes in practice. Results: The post strategy implementation audit results indicated that compliance with clinical guideline recommendations improved considerably. Proper utilization of an appropriate closed drainage system and training of persons maintaining catheters achieved 100% compliance. The guideline recommendation that catheter and drainage bags be changed only when clinically indicated reached 94% compliance. Catheters removed within 24 hours postoperatively improved by more than 50% compliance. Compliance with systemic antimicrobials being clinically indicated and their use justified improved by 25% and documentation on a clinically appropriate indication for ongoing urinary catheterization improved by almost 33.3%. Conclusions: The implementation project was successful in improving nurses' knowledge and skills related to the prevention of CAUTI. A variety of strategies, such as an education program, simple and clear instruments, collaboration with physicians in caring for patients with a high risk of CAUTI, and multiple educational materials can facilitate implementation of evidence based procedures in clinical practice.